Family Support on Blood Pressure in Elderly Hypertension: A Literature Review - Rahayu, Muthia Ridha; Adriani, Rita Benya; Patriyani, Ros Endah Happy (Poltekkes Kemenkes Surakarta, 2023)
Background: Hypertension is a non-communicable disease that mostly occurs in the elderly and can cause serious complications such as stroke and heart disease. One factor that can help manage hypertension in the elderly is family support. This support plays a role in improving adherence to medication, maintaining a healthy diet, and reducing stress that can affect blood pressure. This study aims to examine the relationship between family support and blood pressure management in hypertensive elderly based on a literature review. Methods: This study used the literature review method with guidelines from Grove and Gray EBP. Articles were searched through Google Scholar, Ebsco, and Elsevier databases with the keywords